Legal protection of the trademark - Boudraa, Faiza; Belimane, Yamina (Journal of Human Sciences, 2022)
The trademark is considered one of the most important elements of industrial property in particular, and it is that distinctive sign that merchants place to distinguish their goods or services from their counterparts, to attract consumers to prefer and promote the use or acquisition of their goods or services. The Algerian legislator may intervene to protect the trademark by means of several laws. The most recent of which is Order 03-06 related to trademarks, in order to establish special protection for the trademark. Bearing in mind that the most prominent attacks on it are the attempt to imitate it as a stand-alone industrial property; through a right lawsuit, and the lawsuit of unfair competition to redress Damage to the merchant when the counterfeiter’s action aims to seize the customers of the mark. To deal with this theme, we used the deductive analytical approach and the comparative approach.